Characteristics of Host Trees as Habitat for Ephiphytic Orchids in the Cibereum waterfall Path, Mount Gede Pangrango, West Java - Bela Prapitasari; Ardyan Pramudya Kurniawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
An epiphytic orchid is one type of orchid that has the characteristics of habitat attached to the host tree. Mount Gede Pangrango, especially in the Cibereum waterfall, Selabintana, is a tropical forest area with many large host trees with a lush canopy, causing the epiphytic orchid species to form be abundant in the area. This study aims to determine the type and characteristics of the host tree used as a habitat for epiphytic orchids in the Cibereum waterfall path. The research method is to make ten plots on the right and left sides of the path, with each plot measuring 500x5 m and the distance between plots is 100 m. The results showed that on the Cibereum waterfall path, 33 species of host trees were found, consisting of 20 families. At the same time, the types of orchids found were 31 species from 12 genera. Almost all of the orchid hosts are trees, except for Brassaiopsis glomerulata are shrubs and Cyathea sp are poles. The characteristics of host trees as habitat for epiphytic orchids are: 4-51 m tall, trunk diameter 7-89 cm, canopy width 0-20 m, bark thickness 0-1.2 cm, bark texture rough to medium, generally colored brown, has no sap except for Ficus variegata, the surface of the trunk contains moss, and the epiphytic orchid growth zone on the host tree is mostly found in zones III and IV.